The Activated Charcoal of Hazelnut Shell (Aleurites moluccana) Has Potential Capability to Refining Used Cooking Oil - Desiana Sanang; Luther Kadang; Theodore Y. K. Lulan (Journal of Applied Chemical Science, 2012)
The research that aims to determine the ability of chandlenut shell activated carbon as adsorbent on purification adible frying oil has been done. Frying oil purification process includes of the removal phase seasoning (despicing), neutralization and bleaching using activated carbon. The results showed that the optimum amount of chandlenut shell activated carbon which interacted with adible frying oil on purification process at 0,75 grams, effectively lowering the acid value (0,2984 mg KOH / g), peroxide value (3,2847 meq / Kg), water content (0,1468%) and free fatty acid levels (0,1261%), and increasing numbers saponification (196,2711 mg KOH / g) and also clear oil. However, peroxide value and oil colors result of interacted with the chandlenut shell activated carbon, do not meet the National Standard of Indonesia.